Effects of Patent Ductus Arteriosus on the Hemodynamics of Modified Blalock–Taussig Shunt Based on Patient-Specific Simulation - Xiong, Jiwen; Sun, Qi; Qian, Yi; Hu, Liwei; Tong, Zhirong; Liu, Jinfen; Liu, Jinlong (Frontiers in Physiology, 2021)
The question of preserving the patent ductus arteriosus (PDA) during the modified Blalock-Taussig shunt (MBTS) procedure remains controversial. The goal of the present study was to investigate the effects of the PDA on the flow features of the MBTS to help with preoperative surgery design and postoperative prediction. In this study, a patient with pulmonary atresia and PDA was included. A patient-specific three-dimensional model was reconstructed, and virtual surgeries of shunt insertion and ductus ligation were performed using computer-aided design. Computational fluid dynamics was utilized to analyze the hemodynamic parameters of varied models based on patient-specific anatomy and physiological data. The preservation of the PDA competitively reduced the shunt flow but increased total pulmonary perfusion. The shunt flow and ductal flow collided, causing significant and complicated turbulence in the pulmonary artery where low wall shear stress, high oscillatory shear index, and relative residence time were distributed. The highest energy loss was found when the PDA was preserved. PDA preservation is not recommended during MBTS procedures because it negatively influences hemodynamics. This may lead to pulmonary over-perfusion, inadequate systemic perfusion, and a heavier cardiac burden, thus increasing the risk of heart failure. And it seems to bring no benefit in terms of reducing the risk for thrombosis.